Analysis of goals in 2012 futsal league’s games - Alves, Igor Poffo (2012)
The objective of this study was to analyze how the goals occurred in the first round of the 2012 Futsal League. Studied the actions technical tactics as well as the incidence and the playing time they occurred. The sample consisted of 94 951gols of 190 games in 19 of the first phase of the alloy. Data were recorded in Excel 2007 and adopted the method was quantitative, descriptive observational. In the results, we find that the average goals per game and the league of the study are very close, 4.94 and 5.01 respectively. Shares technical tactics that stood out against the others were counterattacking with 37.25% and 30.85% with positional attack. The dead-ball situations and the use of online goalkeeper, added, resulted in 30.85% of the goals. Regarding time, the numbers in the four times were very close, with a slight difference in the final 10 minutes, where there were more goals. The study serves as a reference on the structure and methodology of training futsal. However, it is necessary to further research on the futsal.